A named GP increases self-reported access to health care services - Lautamatti Emmi; Mattila Kari; Suominen Sakari; Sillanmäki Lauri; Sumanen Markku (BMC, 2022)
Background
Continuity of care strengthens health promotion and decreases mortality, although the mechanisms of these effects are still unclear. In recent decades, continuity of care and accessibility of health care services have both decreased in Finland.
Objectives
The aim of the study was to investigate whether a named and assigned GP representing continuity of care is associated with the use of primary and hospital health care services and to create knowledge on the state of continuity of care in a changing health care system in Finland.
Methods
The data are part of the Health and Social Support (HeSSup) mail survey based on a random Finnish working age population sample of 64,797 individuals drawn in 1998 and follow-up surveys in 2003 and 2012. The response rate in 1998 was 40% (n = 25,898). Continuity of care was derived from the 2003 and 2012 data sets, other variables from the 2012 survey (n = 11,924). The principal outcome variables were primary health care and hospital service use reported by participants. The association of the explanatory variables (gender, age, education, reported chronic diseases, health status, smoking, obesity, NYHA class of any functional limitation, depressive mood and continuity of care) with the outcome variables was analysed by binomial logistic regression analysis.
Results
A named and assigned GP was independently and significantly associated with more frequent use of primary and hospital care in the adjusted logistic regression analysis (ORs 1.53 (95% CI 1.35–1.72) and 1.19 (95% CI 1.08–1.32), p < 0.001).
Conclusion
A named GPs is associated with an increased use of primary care and hospital services. A named GP assures access to health care services especially to the chronically ill population. The results depict the state of continuity of care in Finland. All benefits of continuity of care are not enabled although it still assures treatment of population in the most vulnerable position.